2011
DOI: 10.1186/1471-2318-11-84
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Vulnerable Elders (MOVE): study protocol to evaluate the implementation and outcomes of a mobility intervention in long-term care facilities

Abstract: BackgroundAlmost 90% of residents living in long-term care facilities have limited mobility which is associated with a loss of ability in activities of daily living, falls, increased risk of serious medical problems such as pressure ulcers, incontinence and a significant decline in health-related quality of life. For health workers caring for residents it may also increase the risk of injury. The effectiveness of rehabilitation to facilitate mobility has been studied with dedicated research assistants or exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 97 publications
(97 reference statements)
1
27
0
1
Order By: Relevance
“…Mobility limitations become more prevalent with age, and have been reported to approach 90% in some nursing home settings [25,26], which may subsequently impact ability to perform a gait speed test. One previous study of very old people showed that the ability to perform the gait speed test declined with age in women, with more than half of the female participants aged 95 years or older missing a gait speed value [27].…”
Section: Discussionmentioning
confidence: 99%
“…Mobility limitations become more prevalent with age, and have been reported to approach 90% in some nursing home settings [25,26], which may subsequently impact ability to perform a gait speed test. One previous study of very old people showed that the ability to perform the gait speed test declined with age in women, with more than half of the female participants aged 95 years or older missing a gait speed value [27].…”
Section: Discussionmentioning
confidence: 99%
“…This mixed methods process evaluation was part of the Mobility of Vulnerable Elders (MOVE) clinical trial in which HCAs encouraged LTC residents to complete a simple sit-to-stand activity. 8,9 Knowledge translation interventions were used during this trial to promote the sustainability of the sit-to-stand activity and improve its documentation by HCAs. This process evaluation included interviews, focus groups and a ranking exercise to elicit perceptions of HCAs and facility leaders about the effectiveness and ease of implementation of those KT interventions.…”
Section: Methodsmentioning
confidence: 99%
“…Public health authorities and professional bodies have taken initiatives to develop various outcomes tools to evaluate neurorehabilitation services 8,9 , but there is a less obvious tendency to study the radiological features of the lesions leading to spasticity as they tend to be for more specific entities such as acute stroke 10 which -ideally-should be highlighted during or near admission time to expedite neurorehabilitation assessment and early implementation of treatment to improve outcome, decrease morbidity and length of stay aiming to improve post admission quality of life 11 .…”
Section: Introductionmentioning
confidence: 99%